Towards ensemble asteroseismology of the young open clusters χ Persei and NGC 6910 - Saesen, S.; Pigulski, A.; Carrier, F.; Michalska, G.; Aerts, C.; De Ridder, J.; Briquet, M.; Handler, G.; Kołaczkowski, Z.; Acke, B.; Bauwens, E.; Beck, P. G.; et al. (2010)
As a result of the variability survey in χ Persei and NGC 6910, the number of β Cep stars that are members of these two open clusters is increased to twenty stars, nine in NGC 6910 and eleven in χ Persei. We compare pulsational properties, in particular the frequency spectra, of β Cep stars in both clusters and explain the differences in terms of the global parameters of the clusters. We also indicate that the more complicated pattern of the variability among B-type stars in χ Persei is very likely caused by higher rotational velocities of stars in this cluster. We conclude that the sample of pulsating stars in the two open clusters constitutes a very good starting point for the ensemble asteroseismology of β Cep-type stars and maybe also for other B-type pulsators.
Keywords: Astrophysics - Solar and Stellar Astrophysics; NGC 6910); open clusters and associations: individual (χ Per; Stars: oscillations; techniques: photometric